问题 解答题
计算:
(1)(-7)+(-3)+(+9)+(-1);
(2)(-5)-(-7);
(3)
1
3
-
1
2
-
3
4
+
2
3

(4)(-2
2
5
)×(-
3
4
)÷(-3
3
5
);
(5)
8
81
×6
3
4
-(-
2
7
)÷(-1
5
7
)+(0.5)2
(6)-(-3)2+(-3)2-(-1)3×(
1
3
-
1
2
)÷
1
6
-|-5|.
答案

(1)原式=-7-3+9-1

=-10+9-1

=-1-1

=-2;

(2)原式=-5+7

=2;

(3)原式=

1
3
+
2
3
-
2
4
-
3
4

=1-

5
4

=-

1
4

(4)原式=-

12
5
×(-
3
4
)×(-
5
18

=-

1
2

(5)原式=

8
81
×
27
4
-(-
2
7
)×(-
7
12
)+(
1
2
2

=

2
3
-
1
6
+
1
4

=

8
12
-
2
12
+
3
12

=

9
12

=

3
4

(6)原式=-9+9-(-1)×(-

1
6
)×6-5

=-9+9-1-5

=-6.

解答题
填空题